Analysis of the ν1+ν3 band of T216O and the ν 1 + ν 3 and 2ν2 + ν3 bands of DT16O. (18th August 2022) - Hermann, Valentin; Gaisdörfer, Marcel; Erygina, Alina; Lingnau, Philipp; Schlösser, Magnus; Hase, Frank; Orphal, Johannes
Abstract : We present the ν 1 + ν 3 band of T 2 16 O and the ν 1 + ν 3 and 2 ν 2 + ν 3 bands of DT 16 O that have been analysed for the first time using high-resolution infrared spectra of tritiated water vapour. The spectrum for T 2 16 O has been recorded from a custom-built light-pipe cell at room temperature using a Bruker 125HR Fourier-transform spectrometer at a resolution of 0.025 cm − 1 . For the DT 16 O species, an optimised version of the optical cell with 10 times larger maximum activity with regard to previous studies has been employed. For the ν 1 + ν 3 band of T 2 16 O, we report 206 new experimental line positions in the range from 4415 to 4645 cm − 1 . In the range of 4780– 5175 cm − 1, 356 new experimental line positions of the DT 16 O have been assigned for the ν 1 + ν 3 band and 161 line positions for the 2 ν 2 + ν 3 band. The analysis agrees with previous observations showing a systematic shift of the individual line positions compared to the variationally calculated line positions from the Tomsk database. This shift is depending on the rotational quantum number K a . For each band, the assigned lines were used to determine the spectroscopic constants of the A -reduced Watson-type Hamiltonian. GRAPHICAL ABSTRACT: UF0001